Factors influencing the intention to use information service mashups: An empirical study of digital libraries in China. Issue 4 (1st August 2016) - Yan, Weiwei; Deng, Shengli; Zhang, Yin
Abstract : Purpose: This study aims to examine the factors influencing the adoption intention of information service mashup in digital library (DL). The study is an empirical study on DLs in China. Design/methodology/approach: This paper employs the theory of information service mashup as its theoretical background and applies it to the field of DL to develop the measurement model which is based on technology acceptance model (TAM). A structured questionnaire was developed including the demographic information, the advantages of information service mashup in DL and the Likert evaluation of each construct. As a result, of 303 questionnaires distributed among DL users, 281 were remained as acceptable answers. The data were processed and analyzed with the aid of the SPSS 20.0 and SmartPLS 2.0. Findings: The results show that beyond perceived usefulness and perceived ease of use, both perceived integration and perceived risk have direct impacts on user's intention to adopt information service mashup in DL. Perceived integration has the dramatic positive effects, while perceived risk negatively correlates to adoption intention. Moreover, perceived integration and individualization have positive impacts on perceived ease of use, while network externality positively influences perceived usefulness. Originality/value: Information service mashup is still a relatively new technology in DL. There were few theoretical and empirical studies that examine the user adoption behaviour of the service. This study contributes to existing information service mashup application studies by modifying and extending TAM. The results would help the DL gain a deeper understanding of the factors affecting DL user adoption of information service mashup.